Tacrolimus-Induced Diabetic Ketoacidosis (DKA) in Post Bone Marrow Transplant Patient - Omkar KALIDASRAO CHOUDHARI; Disha SATYA; Naveen GUPTA; Priyanka SONI; Purvish PARIKH; Hemant MALHOTRA (Documenta Haematologica, 2025)
Introduction. Hematopoietic stem cell transplant is an established management in various blood disorders. This contemporary management has improved patient survival; tackling immunosuppression and managing post-transplant complications is of prime importance. Post-transplant Diabetes Mellitus is one of the complications encountered in these patients, and various causes include Calcineurin inhibitors (CNIs), Cytomegalovirus (CMV) viremia, Graft versus host disease (GVHD), and Insulin resistance. Case Presentation. A 20-year-old male known case of severe aplastic anaemia with matched sibling donor (MSD) allogeneic stem cell transplant day + 351 presented in drowsy condition in casualty. His blood sugar level was 584mg/dl, and arterial blood gas (ABG) showed metabolic acidosis. Urine ketones were moderately positive. The patient was diagnosed with Diabetic Ketoacidosis, was managed in the Intensive Care Unit (ICU), gradually recovered with insulin therapy and was discharged. Conclusion. Regular close follow-up is required to detect post-transplant DM(PTDM) for better prognosis.